2018
DOI: 10.1073/pnas.1710779115
|View full text |Cite
|
Sign up to set email alerts
|

Learning to make external sensory stimulus predictions using internal correlations in populations of neurons

Abstract: To compensate for sensory processing delays, the visual system must make predictions to ensure timely and appropriate behaviors. Recent work has found predictive information about the stimulus in neural populations early in vision processing, starting in the retina. However, to utilize this information, cells downstream must be able to read out the predictive information from the spiking activity of retinal ganglion cells. Here we investigate whether a downstream cell could learn efficient encoding of predicti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…Very few experiments and data collections examining NTIC properties in neural systems have yet appeared. To our knowledge, only two studies (Palmer et al, 2015 ; Sederberg et al, 2018 ) coincidentally examined relevant properties in salamander retina; these found that a large group of neural populations of retinal ganglion cells encoded predictive information about external stimuli and also had high self-predictive information about their own future states. This result is consistent with the characteristic of NTIC.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Very few experiments and data collections examining NTIC properties in neural systems have yet appeared. To our knowledge, only two studies (Palmer et al, 2015 ; Sederberg et al, 2018 ) coincidentally examined relevant properties in salamander retina; these found that a large group of neural populations of retinal ganglion cells encoded predictive information about external stimuli and also had high self-predictive information about their own future states. This result is consistent with the characteristic of NTIC.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…The correlations inherent to visual motion mean that the motion trajectory leading up to a particular time (t ≤ 0) provides information about the likely trajectory of motion at later time points (t > 0). This information can then be used to estimate motion trajectories and to guide behavior (Bialek et al, 2006;Palmer et al, 2015;Salisbury and Palmer, 2016;Chalk et al, 2018;Sederberg et al, 2018). The correlations in the motion stimuli used in our study contained this type of predictive information within a time window of approximately ±50 ms ( Figure 3D).…”
Section: Time Scales Of Encoding Match Correlation Structure Of Stimulimentioning
confidence: 74%
“…The efficient coding principle focuses on how the nervous system extracts predictive information from environmental stimuli. Both theories have been supported by experimental evidence, primarily in the visual and auditory systems [9][10][11][12] .…”
Section: Sources Of Predictive Information In Dynamical Neural Networkmentioning
confidence: 89%